Shape and Rule Information Is Reflected in Different Local Field Potential Frequencies and Different Areas of the Primate Lateral Prefrontal Cortex - Sakamoto, Kazuhiro; Kawaguchi, Norihiko; Mushiake, Hajime (Frontiers in Behavioral Neuroscience, 2022)
The lateral prefrontal cortex (LFPC) plays a crucial role in executive function by adaptively storing behavior-relevant information as working memory. Neural mechanisms associated with local field potentials (LFPs) may underlie the adaptive properties of the LFPC. Here, we analyzed how LFPs recorded from the monkey LFPC are modulated by the crucial factors of a shape manipulation task. In this task, the test shape is transformed by manipulating a lever to match the size and orientation of the sample shape. The subject is required to temporarily memorize the rules such as the arm-movement-manipulation relationship and the sample shape to generate the sequential behavior of operations. In the present study, we focused on task variables about shape and rules, and examined among which aspects distinguish the ventral and dorsal sides of the LFPC. We found that the transformed shape in the sample period strongly affected the theta and delta waves in the delay period on the ventral side, while the arm-manipulation assignment influenced the gamma components on the dorsal side. These findings suggest that area- and frequency-selective LFP modulations are involved in dynamically recruiting different behavior-relevant information in the LFPC.